THE USE OF SPELLING BEE GAME TO ENCOURAGE STUDENTS’ VOCABULARY AT SEVENTH GRADE STUDENT OF SMPN 3 PAGIMANA - Wahyuni Bahar; Yuliana Mangendre (English Education Study Program, 2021)
This study aims to find out whether the Spelling Bee Game can improve students' vocabulary mastery. This study used a pre-experimental design. The variables of this research are the Spelling Bee game as the independent variable and the students' vocabulary as the dependent variable. The samples of this research were students of class VIIA and VIIB of SMP Negeri 3 Pagimana, totaling forty-four students. The sampling technique is purposive sampling, which means the sample is selected with a specific purpose. This study uses a test as the main instrument which is divided into pre-test and post-test. Analysis of the data in this study using statistical calculations. The results of this study, the mean value of the pre-test is 34.5, while the post-test is 62.2 and the hypothesis test, the t-counted value is 17.07,